2009
DOI: 10.1002/ajmg.a.32885
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of candidate genes in seven Turkish families with autosomal recessive amelogenesis imperfecta

Abstract: Amelogenesis imperfectas (AI) are a group of inherited defects of dental enamel formation that show both clinical and genetic heterogeneity. Seven Turkish families segregating autosomal recessive AI (ARAI) were evaluated for evidence of a genetic etiology of AI for the seven major candidate gene loci (AMBN, AMELX, ENAM, FAM83H, KLK4, MMP20, and TUFT1). Dental and periodontal characteristics of the affected members of these families were also described. The mean scores of DMFS and dfs indices were 9.7 and 9.6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…Ellis et al [25] defined skeletal open bite as increased gonial and mandibular plane angles in comparison with a control group with Class II malocclusions. According to these diagnostic variables for skeletal open bite and in agreement with previous studies, our findings suggest that the open-bite malocclusion in our AI patients was skeletal in origin [2,4,18,19,21].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Ellis et al [25] defined skeletal open bite as increased gonial and mandibular plane angles in comparison with a control group with Class II malocclusions. According to these diagnostic variables for skeletal open bite and in agreement with previous studies, our findings suggest that the open-bite malocclusion in our AI patients was skeletal in origin [2,4,18,19,21].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, our study identified openbite malocclusion in 35% of the AI population. Becerik et al [4] recently reported anterior open bite in five of ten (50%) Turkish patients with autosomal-recessive AI. Ravassipour et al [2] noted that 42% of the AI population had dental and/or skeletal open-bite malocclusion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Their studies indicated that additional genes are responsible for a significant number of cases of ARAI in the Turkish population (194). …”
Section: Defective Enamelmentioning
confidence: 99%